Cost-effectiveness of dapagliflozin for the treatment of heart failure: a systematic review - Jiang, Zehui; Chen, Dong xiao; Xiao, Cai; Fu, Ying; Zhang, Jun (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to synthesize evidence on the cost-effectiveness of dapagliflozin for heart failure (HF) with all ejection fractions (EF), Including heart failure with reduced ejection fraction (HFrEF), heart failure with mildly reduced ejection fraction (HFmrEF) and heart failure with preserved ejection fraction (HFpEF).MethodsLiterature searches were conducted in English-language databases (PubMed, web of science, Embase, Cochrane Library) and Chinese-language databases (CNKI, Wanfang Data, and Chongqing VIP) to identify studies of dapagliflozin for heart failure. The search was current to 3 October 2024.ResultsTwenty-eight studies were identified in the systematic review and the overall quality was accepted. Studies were conducted across 15 countries including China, UK, US, Japan, South Korea, Singapore, Thailand, Australia, Egypt, Colombia, Philippines, Qatar, Canadian, German, and Spanish. Cost-effectiveness analyses of dapagliflozin were performed for HFrEF patients in all countries, HFpEF patients in the US and China, HFpEF/HFmrEF patients in the UK, Germany, Spain and China and HF patients in the UK, US, Korea and Thailand. Except for one study in Thailand, all studies showed that dapagliflozin is cost-effective. One study in Korea showed that the cost-effectiveness of dapagliflozin in patients with left ventricular EF (LVEF)≤40% was more pronounced than LVEF >40%. Four studies (two HFrEF and one HFpEF in the US and one HFrEF in China) showed that dapagliflozin was more cost-effective than empagliflozin. In the nine diabetes subgroup analyses, seven results showed that dapagliflozin was more cost-effective for patients with diabetes. The incremental cost-effectiveness ratios (ICER)were most sensitive to the cost of dapagliflozin and cardiovascular mortality in the uncertainty analysis.ConclusionDapagliflozin is cost-effective in the treatment of HF with all ejection fractions. The cost-effectiveness of patients with LVEF≤40% (HErEF)was more pronounced than LVEF >40% (HFpEF and HFmrEF). Compared to empagliflozin, dapagliflozin may be more cost-effective.